Sisters in the life : a history of out African American lesbian media-making - Welbon, Yvonne, 1962-; Juhasz, Alexandra (Camera obscura book (Duke University Press), 2018)
From experimental shorts and web series to Hollywood blockbusters and feminist porn, the work of African American lesbian filmmakers has made a powerful contribution to film history. But despite its importance, this work has gone largely unacknowledged by cinema historians and cultural critics. Assembling a range of interviews, essays, and conversations, Sisters in the Life tells a full story of African American lesbian media-making spanning three decades. In essays on filmmakers including Angela Robinson, Tina Mabry and Dee Rees; on the making of Cheryl Dunye's The Watermelon Woman (1996); and in interviews with Coquie Hughes, Pamela Jennings, and others, the contributors center the voices of black lesbian media makers while underscoring their artistic influence and reach as well as the communities that support them. Sisters in the Life marks a crucial first step in narrating the history and importance of these compelling yet unsung artists.